2015
DOI: 10.1111/jfd.12406
|View full text |Cite
|
Sign up to set email alerts
|

miR‐122‐5p as a plasma biomarker of liver injury in fish exposed to microcystin‐LR

Abstract: Recent studies have shown the presence of large amounts of microRNAs (miRNAs; miRs) from damaged cells in the peripheral blood. In this study, we investigated the levels of miRNAs circulating in the blood plasma of whitefish (Coregonus lavaretus) after exposure to microcystin-LR. We used real-time PCR to examine the relative expression of plasma levels of 4 miRNAs (miR-122-5p and let-7c-5p, the liver-enriched microRNAs, miR-148a-3p which promotes the hapatospecific phenotype in mammals, and miR-92a-3p, a cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 35 publications
1
12
2
Order By: Relevance
“…Drug-induced liver injury can be monitored through traditional blood enzymes (ALT, AST) or more sensitively through miRNA quantification. Our previous study on whitefish exposed to MC-LR showed increased liver-specific miRNA plasma levels in fish, which is similar to the outcome acetaminophen induced in mammals (Florczyk et al 2016 ). MiR122-5p levels were elevated as early as 8 h after exposure.…”
Section: Discussionsupporting
confidence: 72%
“…Drug-induced liver injury can be monitored through traditional blood enzymes (ALT, AST) or more sensitively through miRNA quantification. Our previous study on whitefish exposed to MC-LR showed increased liver-specific miRNA plasma levels in fish, which is similar to the outcome acetaminophen induced in mammals (Florczyk et al 2016 ). MiR122-5p levels were elevated as early as 8 h after exposure.…”
Section: Discussionsupporting
confidence: 72%
“…Many studies have revealed that miRNAs are important regulators of liver function in teleost fish ( Her et al, 2011 ; Mennigen et al, 2014 ; Zhang et al, 2014 ; Wang et al, 2016 ). Particularly, miR-122 has been shown as a biomarker of liver injury ( Florczyk et al, 2016 ) and play a role in hepatic lipid metabolism in grass carp ( Wang et al, 2016 ), rainbow trout ( Oncorhynchus mykiss ) ( Mennigen et al, 2014 ), and zebrafish ( Danio rerio ) ( Her et al, 2011 ). Analyses of our deep sequencing data revealed that some miRNAs were differentially expressed in the liver between GIFT fed a HFD and those fed a normal-fat diet (NFD) for 60 days.…”
Section: Introductionmentioning
confidence: 99%
“…The versatile role of miRNAs has sparked the interest of our group in utilizing miRNAs as potential diagnostic [ 35 , 36 ] and prognostic [ 37 , 38 ] biomarkers of MC-LR toxicity and liver injury in fish. In our initial study, we showed that 5 out of 8 miRNAs, MiRlet7c, MiR16a, MiR21a, MiR34a and MiR122, were deregulated in the liver of whitefish ( Coregonus lavaretus ) after short-term (2 d) exposure to MC-LR [ 35 ].…”
Section: Introductionmentioning
confidence: 99%